Counseling on processed herbal plants to reduce blood pressure for the elderly in Wonolelo Hamlet, Bandongan, Magelang - Ni Made Ayu Nila Septianingrum; Halizah Damay Atmoko; Yolla Putry Ramadani; Amalia Khairunnisya; Maudina Puspita Wardani; Tri Anggraeni (Community Empowerment, 2022)
Hypertension is defined as blood pressure with a systolic (TDS) of 140 mm Hg or a diastolic (TDD) of 90 mm Hg. One strategy for preventing hypertension is to check blood pressure once a week and to educate people about herbal plants that can help lower blood pressure. The rise in instances of hypertension in Indonesia is attributable to a lack of public understanding about hypertension screening and treatment. The purpose of this program is to raise public awareness of herbal medicines that can be used to lower blood pressure in Wonolelo Hamlet, Bandongan District, Magelang Regency, as well as promote community skills in developing new herbal preparations to lower blood pressure. The service is provided utilizing the Participatory Rural Appraisal (PRA) method, which incorporates the community in the entire process. This practice has a good impact on the community, since it increases community knowledge and inventiveness about herbal plants, as well as the use of family medicinal herbs like celery, fruit and tree of mahkota dewa.